Identification of senescent cell surface targetable protein DPP4 - Kim, Kyoung Mi; Noh, Ji Heon; Bodogai, Monica; Martindale, Jennifer L; Yang, Xiaoling; Indig, Fred E; Basu, Sandip K; Ohnuma, Kei; Morimoto, Chikao; Johnson, Peter F; Biragyn, Arya; Abdelmohsen, Kotb; et al. (Genes & development, 2017)
Senescent cell accumulation in aging tissues is linked to age-associated diseases and declining function, prompting efforts to eliminate them. Mass spectrometry analysis revealed that DPP4 (dipeptidyl peptidase 4) was selectively expressed on the surface of senescent, but not proliferating, human diploid fibroblasts. Importantly, the differential presence of DPP4 allowed flow cytometry-mediated isolation of senescent cells using anti-DPP4 antibodies. Moreover, antibody-dependent cell-mediated cytotoxicity (ADCC) assays revealed that the cell surface DPP4 preferentially sensitized senescent, but not dividing, fibroblasts to cytotoxicity by natural killer cells. In sum, the selective expression of DPP4 on the surface of senescent cells enables their preferential elimination.